Distribution of the Sciatic nerve in hind limb of Hasmer sheep breed: An anatomical study - Balkaya, Hulya (SaberULA, 2022)
In order to determine the anatomical arrangement of the branches of the sciatic nerve (SN), in Hasmer sheep breed (HSB), five animals were used for this purpose. After opening the body cavities of the cadavers, they were fixed in 10 % formaldehyde solution. The branches of the SN were dissected separately and photographed. In HSB, it was observed that SN passed through the foramen ischiadicum majus together with its branch, caudal gluteal nerve. At the level of the caudoproximal part of the femur, SN gave off its first prominent branch in hind limb, the common root of the rami musculares. After branching the common root of the rami musculares, SN coursed ventrally; and approximately in the middle of the thigh, it was divided into three nerves: caudal sural cutaneous nerve, tibial nerve, and common peroneal nerve. This anatomical study in the HSB will make a demonstrative contribution to understanding the distribution of SN in hind limb, and support further anatomical and surgical studies in this area.
Distribución del nervio ciático en la extremidad posterior de la raza de oveja Hasmer: un estudio anatómico
Keywords: Hasmer sheep; Sciatic nerve; Nerve distribution; Anatomy; Universidad del Zulia (LUZ); Universidad de Los Andes (ULA); Oveja Hasmer; Nervio ciático; Distribución nerviosa; Anatomía; Revista Científica; Revista Científica: Artículos; Medio Ambiente; Revistas